Measures used by stakeholders to mitigate Gender-Based Violence through the Ubuntu philosophy lens in South Africa - Masutha, Thingahangwi Cecilia; Maphula, Angelina; Moloko-Phiri, Salaminah; Matsipane, Molokedi; Gundo, Rodwell (Frontiers in Sociology, 2025)
Gender-Based violence (GBV) is a widespread problem in South Africa, impacting almost every aspect of life. This study aimed to explore measures different stakeholders use to mitigate Gender-Based Violence through the Ubuntu philosophy lens in South Africa. The study's objectives were (1) to explore how the Ubuntu philosophy can be applied to mitigate GBV in South Africa (2) to recommend culturally relevant, community-centered measures to mitigate GBV using Ubuntu principles and foster collective responsibility. The study was conducted in a selected university's boardroom in South Africa. A qualitative approach using explorative, descriptive, and contextual designs was adopted per the research objectives. The population comprised hospital nurses, Thuthuzela Care Center, social workers, psychologists, the South African Police Service (SAPS), the National Prosecuting Authority (NPA), and the Democratic Nursing Organization of South Africa (DENOSA). Eighteen participants were conveniently sampled and consented to participate. Semi-structured questions were used to achieve the objectives of the study. Two focus group discussions were used to collect data. The interviews lasted for 35–45 min and lasted for 1 day. Data was analyzed thematically using Tech's eight steps. Three themes with their sub-themes emerged: information giving, support needed, and Ubuntu principles to mitigate GBV, where reasons for women to remain in abusive relationships, culture and its influences on GBV, and GBV in the workplace were articulated. Mental health support, social development, and services available for the survivors were also deducted from the study as sub-themes. According to the study's findings, raising knowledge of the Ubuntu ideology and GBV may help lessen some types of GBV by promoting Ubuntu's values. This study recommends an interprofessional collaboration on curbing Gender-Based Violence using the Ubuntu philosophy.